A real-world pharmacovigilance analysis of acute renal failure associated with sacubitril/valsartan based on FDA Adverse Event Reporting System (FAERS) - Shiyu Wang; Jinglun Lai; Jiahao Chen; Qingmao Luo; Wenyan Yi; Yingyu Lai (PLoS ONE, 2025)
Background The renal safety profile of sacubitril/valsartan remains debated in clinical practice. To address this uncertainty, we conducted a pharmacovigilance analysis of acute renal adverse events associated with sacubitril/valsartan using the FDA Adverse Event Reporting System (FAERS) database. Methods Using data from the FAERS database, we conducted an observational pharmacovigilance study from the first quarter (Q1) of 2015 to the fourth quarter of 2024 (Q4). The disproportionality analysis was performed using four algorithms: the reporting odds ratio (ROR), the proportional reporting ratio (PRR), the Bayesian confidence propagation neural network (BCPNN), and the multi-item gamma Poisson shrinker (MGPS). Results A total of 16,144,939 adverse events (AEs) were available on FAERS database, among these, 132,255 cases were associated with sacubitril/valsartan, 2,205 cases related to narrow acute renal failure (SMQs) and 3,232 cases with broad SMQs. And sacubitril/valsartan and acute renal adverse showed significant association both in narrow SMQs (ROR = 2.37; PRR = 2.34, χ2 = 1703.73; EBGM05 = 2.26) and the broad SMQs (ROR = 2.55, PRR = 2.51, χ2 = 2941.80, EBGM05 = 2.43). A total of 10 (19.23% of total) positive signals were obtained using the above four algorithms. Median age was 71 years, time to onset was within 30 days, and hospitalization rates of acute renal failure outcomes were 14.33% (narrow SMQs) and 30.69% (broad SMQs). Conclusion The widespread use of sacubitril/valsartan has raised safety concerns, particularly regarding acute renal failure. Our study, leveraging real-world FAERS data, systematically analyzed this association, providing new evidence on acute renal failure risks.